(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
In this paper centers around Swami Vivekananda’s concept of education as fundamental for the improvement of a logical frame of mind, which is in turn important for the advancement of man and society as a rule and of Indian culture specifically. The sort of education Swami Vivekananda considered most essential for Indian culture was ’man-making education’, which would prompt country building. In Swamiji’s point of view, this kind of education had the limit with respect to the social recovery of Indian culture since it should have the capability of purging the human mind of mental debauchery, that is, the propensity towards numbness, laziness and a surrendered disposition which acknowledges anything that is recommended without individual reflection. The prevailing informal frame of mind must be supplanted by a logical mentality, whose constituents were objectivity, discernment and a basic temper.